2023
DOI: 10.3390/cancers15030582
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Evaluation of Soft Tissue Sarcoma Surgical Margins with Indocyanine Green Fluorescence Imaging

Abstract: Soft tissue sarcomas (STS) are rare malignant tumors often associated with poor outcomes and high local recurrence rates. Current tools for intraoperative and definitive margin assessment include intraoperative frozen section and permanent pathology, respectively. Indocyanine green dye (ICG) is a historically safe fluorophore dye that has demonstrated efficacy for intraoperative margin assessment in the surgical management of both breast and gastrointestinal cancers. The utility of ICG in the surgical manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…25 Finally, Gong et al implemented intraoperative margin assessment based on ICG in patients with STSs. 26 The ICG margins matched the permanent pathology margins in 56% of the patients. Larger sample sizes are needed to better quantify optimal dosage, timing, and the effect of histological subtypes.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…25 Finally, Gong et al implemented intraoperative margin assessment based on ICG in patients with STSs. 26 The ICG margins matched the permanent pathology margins in 56% of the patients. Larger sample sizes are needed to better quantify optimal dosage, timing, and the effect of histological subtypes.…”
Section: Discussionmentioning
confidence: 84%
“…Finally, Gong et al. implemented intraoperative margin assessment based on ICG in patients with STSs 26 . The ICG margins matched the permanent pathology margins in 56% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Another study described the utilization of ICG in 18 patients with STS, which showed 89% specificity in tumor margins. 20 Nevertheless, some concerns with ICG include its cost implications due to early admission for administration and its nonspecific nature that may lead to over-resections. In contrast, 5-aminolevulinic acid (5-ALA) has shown promising utility in FGS for malignant gliomas, and is approved by the FDA.…”
Section: Fluorescence-guided Surgerymentioning
confidence: 99%
“…In an extended case series, the utilization of ICG in patients with high‐grade sarcomas found a reduction in positive margin rate 19 . Another study described the utilization of ICG in 18 patients with STS, which showed 89% specificity in tumor margins 20 . Nevertheless, some concerns with ICG include its cost implications due to early admission for administration and its nonspecific nature that may lead to over‐resections.…”
Section: Emerging Technologymentioning
confidence: 99%